NILAI-NILAI ISLAM DALAM UPAYA PENCEGAHAN FRAUD - Alfian, Nurul (JURNAL AKUNTANSI DAN INVESTASI, 2016)
The objective of this paper is to analyze the influence of islamic values to prevent fraud. A literature review on various types of fraud since the early era of Islam were identified and discussed.  This research was condusted by comparing the prevention of fraud in general and seen from the perspective of islam with the hope to be an effort to minimize fraud that occurred.  This study reveals that fraud led to the rights of recipients being denied, wastage, inefficiency and rampant white collar crime if left unchecked. Hence, the study proposes several treatments in minimizing fraud. Islam promotes just distribution and ethics in any transactions. Those practicing fraud or mismanagement should be penalized and those who are ethical in managing this fund shall be rewarded for their credibility and good value which is to ensure the effectiveness and efficiency of managing those funds for the benefit of the society. And through the Qur’an and Hadith can be a part for Muslimss to be able to avoid the occurance of fraud